2020
DOI: 10.1186/s12872-020-01620-z
|View full text |Cite
|
Sign up to set email alerts
|

Identifying Phenogroups in patients with subclinical diastolic dysfunction using unsupervised statistical learning

Abstract: Background: Subclinical diastolic dysfunction is a precursor for developing heart failure with preserved ejection fraction (HFpEF); yet not all patients progress to HFpEF. Our objective was to evaluate clinical and echocardiographic variables to identify patients who develop HFpEF. Methods: Clinical, laboratory, and echocardiographic data were retrospectively collected for 81 patients without HF and 81 matched patients with HFpEF at the time of first documentation of subclinical diastolic dysfunction. Densityb… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 18 publications
(54 reference statements)
0
12
0
Order By: Relevance
“…Sabbah et al did not attempt to identify a new HFpEF clinical classification but rather to use ML analytic techniques to determine whether unique inflammation patterns exist in HFpEF and are associated with clinical severity or profibrotic state (Sabbah et al, 2020[ 99 ]). One study enrolled patients with echocardiographic evidence of diastolic dysfunction and evaluated whether they did or did not progress to have clinical evidence of heart failure (HFpEF) (Kaptein et al, 2020[ 53 ]). One study focused on comparing different ML models rather than trying to identify phenogroups (Angraal et al, 2020[ 4 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Sabbah et al did not attempt to identify a new HFpEF clinical classification but rather to use ML analytic techniques to determine whether unique inflammation patterns exist in HFpEF and are associated with clinical severity or profibrotic state (Sabbah et al, 2020[ 99 ]). One study enrolled patients with echocardiographic evidence of diastolic dysfunction and evaluated whether they did or did not progress to have clinical evidence of heart failure (HFpEF) (Kaptein et al, 2020[ 53 ]). One study focused on comparing different ML models rather than trying to identify phenogroups (Angraal et al, 2020[ 4 ]).…”
Section: Methodsmentioning
confidence: 99%
“…Due to the complexity of the data and heterogeneity of patients, the identification of distinct clinical phenotypes using machine learning may allow for more targeted diagnostics and personalized therapeutic options [ 119 ]. Cohen et al identified three distinct phenogroups that displayed differences in circulating biomarkers, cardiac/arterial characteristics, and prognosis among TOPCAT trial participants [ 120 ].…”
Section: Future Perspectivesmentioning
confidence: 99%
“…The DL approach showed higher AUC than the 2016 American Society of Echocardiography guideline-based left ventricular grades [60] for predicting elevated left ventricular filling pressure (0.883 vs. 0.676). Kaptein et al [61] proposed an unsupervised learning approach to identify subgroups of patients with asymptomatic diastolic dysfunction, where three subgroups were identified. Similarly, in [62], a model-based clustering on clinical and echocardiogram variables in 320 HFpEF patients was applied, from which six phenogroups were derived.…”
Section: Deep Learning In Hf Diagnosismentioning
confidence: 99%